2015
DOI: 10.1248/yakushi.14-00244
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of Anionic Uremic Toxins in Hemodialysis Patients and Their Effects on Protein Binding of Pravastatin

Abstract: Uremic toxins (UTs) accumulate in the body of hemodialysis patients. UTs often exert unfavorable eŠects on patients and cause signiˆcant interactions with clinically relevant drugs. In this study, we assayed plasma concentrations of three typical anionic UTs, indoxyl sulfate (IS), 3-indoleacetic acid (IA), and 3-carboxy-4-methyl-5-propyl-2-furanpropionic acid (CMPF), in 20 hemodialysis patients and 5 healthy volunteers. Moreover, the eŠects of these anionic UTs on the binding of pravastatin to human serum albu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…However, the fact that plasma levels of CMPF were almost the same before and immediately after HD (Table 2) and that the HD clearance of these three UTs was well correlated with their protein binding rate 12) could imply the relatively small in‰uence of membrane adsorption on the results in this study.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…However, the fact that plasma levels of CMPF were almost the same before and immediately after HD (Table 2) and that the HD clearance of these three UTs was well correlated with their protein binding rate 12) could imply the relatively small in‰uence of membrane adsorption on the results in this study.…”
Section: Discussionmentioning
confidence: 70%
“…Consistent with the previous literature, 8 11) the results obtained from the study demonstrated that the greatest diŠerence in the mean plasma levels between HD patients and healthy subjects was for IS. 12) Our recent study also showed that IS was capable of modulating the binding of pravastatin to albumin, indicating an interaction at albumin binding site II. 12) As dyslipidemia is frequent in HD patients, hydroxymethylglutaryl-CoA (HMG-CoA) reductase inhibitors are often prescribed to them.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations